Main concepts of organizing the processes of erecting structural elements of buildings in the system of modern construction production - Martyniuk, I; Ustinov, Ye.; Kovalenko, V.; Sokurov, A.; Bovanenko, D. (Ways to Improve Construction Efficiency, 2024)
The organization of processes for erecting structural elements of buildings occupies a key position in the system of modern construction production, since the efficiency of these processes determines the quality, duration, and economic feasibility of project implementation. This study reveals the main concepts that form the methodological basis of construction process management. Among them are traditional technological approaches, modern models of flow organization, the application of information technologies, and methods of automation that ensure the integration of various construction stages into a single system. Considerable attention is given to forming a rational sequence of assembling structural elements, selecting optimal resources, and utilizing modern construction materials. The study emphasizes that effective organization of erection processes is impossible without considering external environmental factors, including economic fluctuations, regulatory restrictions, and labor market conditions. Innovative concepts of construction process management are also discussed, particularly the application of BIM technologies, digital platforms for resource management, and advanced logistics schemes. These approaches make it possible not only to improve the quality of construction work but also to minimize risks associated with deviations in project timelines and costs. A separate focus is placed on integrating the principles of sustainable development into the construction production system. The use of energy-efficient technologies, recycled materials, and environmentally safe construction methods is identified as an essential component of modern organizational processes. Such practices contribute not only to increasing production efficiency but also to forming a new culture of construction activity oriented toward long-term environmental responsibility. The findings confirm that a systemic approach to organizing the processes of erecting structural elements of buildings ensures higher product quality, reduced costs, and accelerated construction timelines. The defined concepts can serve as a methodological foundation for further scientific research and practical implementation in the activities of construction companies striving to achieve competitive advantages under modern market conditions.